Kendala-Kendala yang Dihadapi dalam Pengawasan Penggunaan Lampu sebagai Alat Bantu Penangkapan Ikan di Kelurahan Pasia Nan Tigo Kota Padang - Mifthahul Rizka; Fitri Eriyanti (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
This study aims to describe the obstacles faced in monitoring the use of lights as a fishing aid in Pasia Nan Tigo Village, Padang City. The theory used by Kadarman is an important standard for measuring in surveillance research. The method used is a descriptive method with a qualitative approach and purposive sampling technique for selecting informants. The data were collected by means of observation, interview and documentation study techniques. The results of this study indicate that the obstacles faced in monitoring the use of lights as a fishing aid in Pasia Nan Tigo Village, Padang City are lack of supervisors (HR), lack of budget, inadequate facilities and infrastructure and lack of socialization.